Marine ecosystem extent and condition pilot accounts for Finland - Elina Virtanen; Louise Forsblom; Liisa Saikkonen; Susanna Jernberg; Markku Viitasalo; Soile Kulmala (One Ecosystem)
Ecosystem accounting provides a standardised framework for evaluating the economic value of ecosystems to society. Following the international accounting standard, System of Environmental Economic Accounting – Ecosystem Accounting (SEEA EA), we present first marine ecosystem extent pilot accounts for Finland, based on three habitat classification systems: the Marine Strategy Framework Directive (MSFD), the EU Habitats Directive (HD) and the IUCN Red List of Ecosystems (RLE). We assess their condition using indicators from the Water Framework Directive, which measure ecosystem quality through biological, ecological and physico-chemical parameters.We found that MSFD habitats have the largest extent, exceeding the areas covered by HD and RLE habitats. A large portion of the assessed habitats, particularly in the inner archipelago and shallow areas close to shore, were in poor condition, reflecting the eutrophication status of coastal waters. We identify considerable challenges in reporting marine ecosystem extent and condition accounts, which most likely recur across (European) countries. For instance, MSFD habitats are rather coarse for accurately reporting ecosystem extents, potentially overlooking declines in ecosystem condition, while HD habitats cover only a subset of habitats. RLE habitats provide more ecological detail, although they may be less compatible with classifications used in other countries.Our research provides a baseline for future ecosystem accounts and emphasises the need for improved data and methods to enhance the accuracy and comparability of marine ecosystem assessments. Additionally, we discuss the compatibility of SEEA EA with EU policy reporting requirements, the spatial scale of reporting ecosystem extents and condition and highlight the limitations of current habitat classifications in representing the full diversity of marine ecosystems. The findings underscore the importance of integrating multiple habitat classification systems, development of crosswalks between habitat classifications and monitoring frameworks to ensure comprehensive and accurate ecosystem accounts.